Algae of salt-marshes in Chongar Peninsula (Sivash) (CHORNOMORSKI BOTANICAL JOURNAL, 2009)
Species of algae found in Chongar Peninsula are listed together with data on their distribution in different geographical zones and biotopes of Ukraine.
Keywords: algae, ChongarPeninsula, alkaline soil (salt-marshes), not salted soils, phytocenoses, geographical zones of Ukraine.